Lack of formyl peptide receptor 1 and 2 leads to more severe inflammation and higher mortality in mice with of pneumococcal meningitis. Issue 3 (November 2014) - Oldekamp, Sandra; Pscheidl, Sebastian; Kress, Eugenia; Soehnlein, Oliver; Jansen, Sandra; Pufe, Thomas; Wang, Ji Ming; Tauber, Simone C.; Brandenburg, Lars‐Ove
Summary Bacterial meningitis is, despite progress in research and the development of new treatment strategies, still a cause of severe neuronal sequelae. The brain is protected from penetrating pathogens by both the blood–brain barrier and the innate immune system. The invading pathogens are recognized by pattern recognition receptors including the G‐protein coupled formyl peptide receptors (FPRs), which are expressed by immune cells of the central nervous system. The expression of FPRs is up‐regulated during bacterial meningitis, but the consequence on the progression of inflammation and impact on mortality are far from clear. Therefore, we used mFPR1 and mFPR2‐deficient mice to investigate the effects on inflammation, bacterial growth and mortality in a mouse model of pneumococcal meningitis. Our results revealed increased bacterial burden, increased neutrophil infiltration and higher mortality in mFPR1/2‐deficient mice in comparison to wild‐type mice. The mFPR1‐ or mFPR2‐deficient mice also showed significantly increased glial cell density, whereas the immune responses including the expression of anti‐inflammatory cytokines and antimicrobial peptides were decreased in bacterial meningitis. Taken together, the results suggest that FPR1 and FPR2 play an important role in the innate immune responses against Streptococcus pneumoniae within the central nervous system and the lack of the receptors leads to a dysregulation of the inflammatory response compared with wild‐type mice.